Impact of Sleep Quality on the Association Between Unease and Physical Exercise During Initial Stages of COVID-19 Pandemic in India - Bajaj S; Blair KS; Zhang R; Bashford-Largo J; Dobbertin M; Blair RJ (Nature and Science of Sleep, 2020)
Sahil Bajaj,1,2 Karina S Blair,1,2 Ru Zhang,1,2 Johannah Bashford-Largo,1,2 Matthew Dobbertin,1,2 R James Blair1,2 1Multimodal Clinical Neuroimaging Laboratory (MCNL), Center for Neurobehavioral Research, Boys Town National Research Hospital, Boys Town, NE, USA; 2Program for Trauma and Anxiety (PTAC), Center for Neurobehavioral Research, Boys Town National Research Hospital, Boys Town, NE, USACorrespondence: Sahil BajajCenter for Neurobehavioral Research, Boys Town National Research Hospital, 14015 Flanagan Blvd. Suite #102, Boys Town, NE, USAEmail sahil.bajaj@boystown.org